(untitled) (Repertorio Científico, 2020)
Two sources of green manure, Mucuna pruriens and Crotalaria spectabilis were used in three different doses: 100, 150 and 250 g/m2. It was possible to determine the dose of 100 g / m2 with M.pruriens as the best in yield, even better than the commercial control and other treatments, also with an acceptable grain quality, also contributing with a better CICE, a lower acidification of the soil and a good incorporation of organic matter to the soil. Other effects and factors involved under the conditions of this trial are discussed